Microbial Diseases in the Teaching-learning Process of Deaf People: A Possible Dialogue - Roberta Silva Rizzo; Lydia Dayanne Maia Pantoja; Jeanne Barros Leal de Pontes Medeiros; Germana Costa Paixão (Universidade Federal de Santa Maria (UFSM), 2014)
Special Education remains a major challenge in society. Thus, many methodologies and didactic-pedagogic resources have been deployed in order to further the teaching and learning process in different subjects, with emphasis on Science teaching. By understanding the importance of diseases caused by microorganisms, the game titled "Knowing the unseen world - challenging signal" was conceived as a didactic proposal to inform and enlighten deaf students from Elementary School on this subject, applying visual tools. Therefore, its construction took the National Curriculum Parameters (NCP) for Natural Sciences as a guiding, and the development of the graphic art consisted of simple and low cost materials. As a result, it was obtained a teaching resource with signs of LIBRAS that meets the objectives and contents that addresses of the three main themes of the NCPs. So, this is a suggestion to work the microbial content in a less abstract and more attractive form to deaf students, providing an opportunity to address issues specified in science curriculum in order to support the teaching-learning process focused on scientific literacy and the appropriation of knowledge related to the development of skills and abilities necessary to the current society.